Atividade respiratória em diferentes espécies s como método alternativo para avaliação do vigor - Dode, Juliana de Souza (2011)
This study aimed to describe and analyze the efficiency of the method of Pettenkofer in determining the respiratory activity for the differentiation of seeds lots on its vigor. Five lots of soybean seeds cv. Taura, wheat cv. Cd115 and sunflower cv. MG2 were used. Besides the determination of respiratory activity, the following tests were conducted as reference: germination, first count of germination, electrical conductivity, seedlings emergence, length of the shoot and root, and dry mass. The results of reference tests and respiratory activity of seeds allowed the classification of lots at different levels of physiological quality. The timing of soaking and permanence of soybean, wheat and sunflower, in the equipment of Pettenkofer was enough to provide the distinction of lots. According to the results, it appears that lots of high vigor show more respiratory activity than the lower vigor. The determination of respiratory activity, for the method of Pettenkofer, is efficient, quick and useful as alternative test in the differentiation of vigor of lots, of soybean seeds cv. Taura, wheat cv. Cd115 and sunflower cv. MG2